THE EFFECT OF PRICE AND PROMOTION ON USER LOYALTY OF ONLINE TRANSPORTATION SERVICES (GRAB) IN THE TIME COVID-19 PANDEMIC - Rini Astuti; Roby Randyka (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study was to determine the effect of price and promotion on Loyalty of Online Transportation Service Users (Grab) during the covid 19 pandemic (study on students of the Faculty of Economics and Business, University of Muhammadiyah North Sumatra) either partially or simultaneously.The approach in this study uses an associative approach. The population in this study were all students of the Faculty of Economics and Business, University of Muhammadiyah North Sumatra who used online transportation services (Grab). The sampling technique in this study used the zikmund formula so that a sample of 100 people was obtained. The data collection techniques used the questionnaire distribution method with multiple linear regression analysis techniques using the IBM SPSS 21 analysis tool.Based on the results of the study indicate that promotion has a significant influence on customer loyalty of online transportation services users (Grab) on students of the Faculty of Economics and Business, University of Muhammadiyah North Sumatra. Pricse has a significant effect on customer loyalty of online transportation services users (Grab) on students of the Faculty of Economics and Business, University of Muhammadiyah North Sumatra. Promotions and prices have a significant influence on customer loyalty using online transportation services (Grab) for students of the Faculty of Economics and Business, University of Muhammadiyah North Sumatra.Keyword: Keywords: Price, Promotion, Loyalty